Consumer awareness and green cosmetics among Samarinda’s Gen Z - Sary, Kezia Arum; Purwanti, Silviana; Zulfiani, Dini; Ferdianto Putra, R. Yuda; Khotimah, Husnul (Faculty of Communications Science, Dr. Soetomo University, 2025)
This study aims to analyse the influence of Green Consumer Knowledge (GCK), Consumer Social Responsibility (CnSR), and Green Advertising (GA) on green purchasing behaviour (Green Purchase Behaviour) among Generation Z in Samarinda, Kalimantan. A quantitative approach was used with a survey method through an online questionnaire distributed to 189 respondents aged 18-25 years in Samarinda City. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results showed that GCK significantly influenced Green Purchase Behaviour, both directly and through the partial mediation role of CnSR. This suggests that consumer knowledge of green products increases social awareness and encourages more environmentally responsible purchasing decisions. In addition, GA was shown to positively moderate the relationship between CnSR and Green Purchase Behaviour, indicating that sustainability-focused advertising strengthens the influence of social responsibility on consumer purchasing decisions. This study concludes that the combination of GCK, CnSR, and GA is a key driver in promoting sustainable consumption among Generation Z. Practical implications of this study include the importance of consumer education, corporate collaboration with NGOs to improve CnSR, and transparent and credible advertising strategies to avoid scepticism related to greenwashing. This study is limited to the cosmetics sector and the student population in Samarinda, so generalisation to other sectors or regions may be limited. Further research is recommended to involve non-student Generation Z and more diverse product categories.